ChemInform Abstract: Vinyl Azides as Versatile Synthons for the Synthesis of Nitrogen‐Containing Heterocycles. Issue 36 (September 2015) - Ni, Hangcheng; Zhang, Guolin; Yu, Yongping
Abstract Review: 109 refs.